A Pilot Study of Significant Environmental Aspects Analysis on Coastal Fishing Port ‘Pondokdadap’ Malang Indonesia - Agus Dwiyanto; Achmad Wicaksono; Bagyo Yanuwiadi (Indonesian Journal of Environment and Sustainable Development, 2019)
This research aimed to analyze significant environmental aspects of Coastal Fishing Port (PPP) Pondokdadap, Malang, East Java. The significant environmental aspect analysis was undertaken as an initial step in implementing the Eco-Fishing Port concept or managing an environmentally sound fishing port. The analysis was undertaken using the Strategic Overview of Significant Environmental Aspects (SOSEA) method. This method is a method of Ecoports Foundation in identifying the impacts of port management, tailored to the conditions and activities of fishing ports. Based on the results of calculation and analysis of the environmental impact factors with the value range of 1-10, there were 5 (five) significant environmental aspects obtained in the management of PPP Pondokdadap, namely: waste production (7.3); employment absorption (7.0); water pollution (6.8); ship waste production (6.6); and liquid waste (wastewater) production (6.0). In broad outline, significant environmental aspects occur because the prevailing policy and regulation have not been implemented and undertaken in the environmental management activities in PPP Pondokdadap, excluding the aspect of employment absorption occurring within 3-4 months due to natural factors, i.e. non-fish season. Significant environmental aspect management that must be done by the managers of PPP Pondokdadap to realize the Eco-Fishing Port concept implementation include the fulfillment of facility and infrastructure standards according to the prevailing rules, regulation implementation and discipline enforcement, coaching and socialization, continuous environmental aspect monitoring, and procedural preparation of significant environmental aspect management.Keywords: Eco-Fishing Port, PPP Pondokdadap, Significant environmental aspect, SOSEA